2013
DOI: 10.1016/j.jneuroim.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine potentiates proinflammatory responses of human vaginal epithelial cells

Abstract: The vaginal epithelium provides a barrier to pathogens and recruits immune defenses through the secretion of cytokines and chemokines. Several studies have shown that mucosal sites are innervated by norepinephrine-containing nerve fibers. Here we report that norepinephrine potentiates the proinflammatory response of human vaginal epithelial cells to products produced by Staphylococcus aureus, a pathogen that causes menstrual toxic shock syndrome. The cells exhibit immunoreactivity for catecholamine synthesis e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The latter results suggest that the NFκB/IκBα signaling pathway would not be involved in the effect of dopamine in human macrophages. In line with our results, Brosnahan et al [50] and Evans et al [51] have demonstrated in epithelial cells that the catecholamine noradrenaline, via β-AR, increases IL-8 levels by mechanisms that are independent of NFκB, involving, among others, the activation of the adenylate cyclase, the mitogen-associated protein kinase, and the PI-3-kinase signaling pathway. Furthermore, the MAPK and ERK signaling pathways have been demonstrated to be involved in the dopamine-driven regulation of angiogenesis in normal and tumor tissues [34, 52].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The latter results suggest that the NFκB/IκBα signaling pathway would not be involved in the effect of dopamine in human macrophages. In line with our results, Brosnahan et al [50] and Evans et al [51] have demonstrated in epithelial cells that the catecholamine noradrenaline, via β-AR, increases IL-8 levels by mechanisms that are independent of NFκB, involving, among others, the activation of the adenylate cyclase, the mitogen-associated protein kinase, and the PI-3-kinase signaling pathway. Furthermore, the MAPK and ERK signaling pathways have been demonstrated to be involved in the dopamine-driven regulation of angiogenesis in normal and tumor tissues [34, 52].…”
Section: Discussionsupporting
confidence: 93%
“…The activation of catecholaminergic receptors is known to modulate the activity of different immune cells involving the activation of transcription factors such as NFκB. It has been described that adrenaline and noradrenaline induce the production of proinflammatory cytokines involving pathways that are either dependent [3] or independent of the transcription factor NFκB [50]. In this work, we have demonstrated, in THP-1 macrophages, that dopamine increases the production of IL-8 without increasing the levels of NFκB in the nuclear fraction.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the discharge of norepinephrine (noradrenaline) from sympathetic nerve terminals. An elegant series of in vitro experiments by Brosnahan et al has demonstrated that two vaginal epithelial cell lines can bind exogenous norepinephrine as well as secrete both norepinephrine and dopamine. Furthermore, although norepinephrine by itself did not induce a pro‐inflammatory immune response in the vaginal epithelial cells, it significantly enhanced the release of cytokines if immune system activators were also present.…”
Section: Stress and Lactobacillimentioning
confidence: 99%
“…Glucocorticoids also facilitates immunosuppression by inhibiting proliferation, migration and cytotoxicity of lymphocytes and leukocytes, and secretion of IL-2 and IFN-γ ( 73 ). On the other hand, stress-induced epinephrine and norepinephrine bind to adrenergic receptors, activate cAMP and stimulate the transcription of genes encoding for a variety of inflammatory mediators ( 9 , 80 ). Higher stress scores correlate with higher levels of IL-6 and TNF-α; and with low levels of the anti-inflammatory cytokine IL-10 ( 5 ).…”
Section: Pathogenesis Of Stress-induced Vaginal Dysbiosismentioning
confidence: 99%
“…This occurs through the release of CRH, which stimulates sympathetic nerve terminals and the SAM axis to release norepinephrine. Norepinephrine can enter the vagina from the bloodstream and is locally secreted by vaginal epithelial cells to which it binds ( 80 ). Though the vaginal epithelial cells in this in vitro experiment were exposed to a high range of norepinephrine concentrations (1-10 μM), this may not differ significantly from the in vivo environment.…”
Section: Pathogenesis Of Stress-induced Vaginal Dysbiosismentioning
confidence: 99%